Preoperative serum CA 125 is associated with myometrial and cervical invasion in endometrial carcinoma - Abu Bakar, Nur Aini; Osman, Malina; Hussin, Huzlinda (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Endometrial carcinoma is the most common gynaecological malignancy in developed countries and the sixth most common cancer among women worldwide. Cancer staging is vital in treatment decisions and the prediction of prognoses, and is based on imaging studies, histological results and surgery. Therefore, a simple and fast preoperative tool to predict the precise cancer stage of patients is needed. CA 125, a cancer antigen is used in assessing therapeutic response and cancer surveillance in endometrial carcinoma. However, this tumour marker is not routinely performed in the mentioned circumstances. Studies have shown that preoperative CA 125 was significantly high in patients in a higher stage of endometrial cancer. Thus, this study aims to assess the primary role of CA 125 in predicting the stage of endometrial carcinoma, by correlating preoperative serum CA 125 with clinicopathological parameters. Method: The retrospective data of endometrial carcinoma cases consisting of demographic and clinicopathological parameters as well as preoperative serum CA 125 levels were retrieved from Laboratories Information System (LIS) at Hospital Selayang, Selangor, Malaysia, from January 2000 until June 2016. Only 20 cases fulfilled the inclusion and exclusion criteria. Preoperative serum CA 125 was correlated with demographic and clinicopathological parameters, and was analysed using a Kruskal-Wallis test. Results: There was a significant association between elevated serum CA 125 with myometrial and cervical stroma invasion in endometrial carcinoma (p<0.05). Conclusion: Preoperative serum CA 125 is a useful marker in predicting early stages of endometrial carcinoma, and plays a role in pre-operative cancer staging in endometrial carcinoma.